2000
DOI: 10.1046/j.1365-2923.2000.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical skills in early postgraduate medical trainees: patterns of acquisition of confidence and experience among junior doctors in a university teaching hospital

Abstract: Early postgraduate medical trainees in a Sydney teaching hospital acquire high levels of confidence and experience in most skill areas after two years of training. The first postgraduate year is particularly significant for the development of clinical skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 3 publications
0
34
0
5
Order By: Relevance
“…So, here again we see a difference between objectively measured and self-assessed growth. From the literature we know that a direct relation between self-assessed and objectively measured clinical competence seems not to exist (Kegel-From, 1975;Marel et al, 2000;Speechly et al, 1994). Our study shows that also the growth of both of them during training seems not to be related to each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, here again we see a difference between objectively measured and self-assessed growth. From the literature we know that a direct relation between self-assessed and objectively measured clinical competence seems not to exist (Kegel-From, 1975;Marel et al, 2000;Speechly et al, 1994). Our study shows that also the growth of both of them during training seems not to be related to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Even repeated personal feedback based on objective knowledge and skills scores did not improve the accuracy (Jansen et al, 1998). From these findings it may be concluded that self-assessment of clinical competence apparently reveals to what extent someone considers her/ himself competent (self-perceived competence) (Kegel-From, 1975;Marel et al, 2000;Speechly et al, 1994) rather than actual clinical competence (Calhoun et al, 1990;DiMatteo and DiNicola, 1981;Jansen et al, 1998;Johnson and Cujec, 1998;Purdy, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…The relationship between inadequate educational preparation in medical and dental schools and the difficulties experienced by this patient population in gaining access to community based heath services was emphasized in an additional report (Fenton et al, 2003). Essentially, clinical experience with a given patient population increases the confidence of clinicians to treat that population (Marel et al, 2000;Ferrini and Klein, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that PGY-2s in this study were more confident on certain exam skills than incoming interns but performed at the same level on the CE might reflect a lack of emphasis on physical diagnosis teaching and practice prior to the start of the ACE curriculum. This gap between confidence and competence is an important one to address for trainees, as it directly impacts the safety and quality of patient care [37,38].…”
Section: Discussionmentioning
confidence: 99%